2019
DOI: 10.1249/mss.0000000000002180
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Physical Activity Determines Vascular Function in Late Postmenopausal Women

Abstract: Introduction The study evaluated the role of lifelong physical activity for leg vascular function in postmenopausal women (61 ± 1 yr). Method The study design was cross-sectional with three different groups based on self-reported physical activity level with regard to intensity and volume over the past decade: inactive (n = 14), moderately active (n = 12), and very active (n = 15). Endothelial-dependent and smooth muscle-dependent leg vascular function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…This lack of a change in FMD with training in late post-menopausal women is in agreement with studies reporting no change in brachial artery FMD after training in women past menopause (Pierce et al, 2011;Moreau et al, 2013;Santos-Parker et al, 2017). In contrast, microvascular function, as assessed by femoral arterial infusion of either acetylcholine or a prostacyclin analog, in recent postmenopausal women has been shown to be improved by intense aerobic training similar to the current study (Nyberg et al, 2016) and has also been shown to be higher in life-long trained than in sedentary older women (Gliemann et al, 2020). The current finding on absence of training induced improvements in FMD with intense aerobic training suggests that intensity of aerobic training is not a determining factor for the FMD response in this population.…”
Section: Discussionsupporting
confidence: 90%
“…This lack of a change in FMD with training in late post-menopausal women is in agreement with studies reporting no change in brachial artery FMD after training in women past menopause (Pierce et al, 2011;Moreau et al, 2013;Santos-Parker et al, 2017). In contrast, microvascular function, as assessed by femoral arterial infusion of either acetylcholine or a prostacyclin analog, in recent postmenopausal women has been shown to be improved by intense aerobic training similar to the current study (Nyberg et al, 2016) and has also been shown to be higher in life-long trained than in sedentary older women (Gliemann et al, 2020). The current finding on absence of training induced improvements in FMD with intense aerobic training suggests that intensity of aerobic training is not a determining factor for the FMD response in this population.…”
Section: Discussionsupporting
confidence: 90%
“…All cross-sectional studies compared trained versus untrained postmenopausal women (Gliemann, Rytter et al, 2020;Hagmar et al, 2006;McKechnie et al, 2001;Pierce et al, 2011;Sanders et al, 2015;Santos-Parker et al, 2017;Serviente & Witkowski, 2019), however, one study also compared trained and untrained men (Pierce et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…There remain inconsistencies across cross-sectional studies as postmenopausal women who were habitually active or elite endurance athletes demonstrated higher (Gliemann, Rytter et al, 2020;Hagmar et al, 2006;McKechnie et al, 2001;Sanders et al, 2015), similar (McKechnie et al, 2001;Pierce et al, 2011;Santos-Parker et al, 2017) or lower (Serviente & Witkowski, 2019) endothelial function compared to inactive postmenopausal women. This contrasts with meta-analysis findings that older athletes generally have higher endothelial function compared to untrained older adults (Montero et al, 2014(Montero et al, , 2015.…”
Section: Impact Of Habitual Aerobic Trainingmentioning
confidence: 99%
“…According to the latest concept of cardiovasomobility, the maintenance of health and quality of life is related to the cardiovascular and skeletal muscle systems, and is linked to physical activity ( Trinity et al, 2022 ). Indeed, many studies demonstrate that lifelong exercise is associated with preserved cardiovascular and musculoskeletal function ( Iversen et al, 2011 ; Fiuza-Luces et al, 2018 ; Gries et al, 2018 ; Gliemann et al, 2020 ), whereas a sedentary lifestyle is accompanied by cardiovascular and skeletal muscle dysfunction that accelerates the onset of varied diseases ( Booth et al, 2017 ). The implementation of physical activity as a daily health requirement seems to be especially important regarding aging, since age is an independent risk factor of CVD ( Benjamin et al, 2017 ).…”
Section: Survey Methodologymentioning
confidence: 99%